Design of Bidirectional DC-DC Converter for Photovoltaic Charging System - Muhammad Farhan Rizky; Muhammad Syahril Mubarok; Herlambang Setiadi; Nur Vidia Laksmi B. (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
This paper proposes a bidirectional DC-DC converter designed for photovoltaic charging systems. The converter aims to efficiently charge batteries while maintaining stable DC voltage and current output. It can convert DC power from solar panels to charge the battery and deliver DC power from the battery to the connected DC bus. The control method for the converter utilizes PI control to achieve a constant output current and voltage. The simulations were conducted using MATLAB/Simulink software, optimizing the converter’s topology, parameters, and controls according to the requirements of the PV charging system. Simulations validated the converter’s performance under various conditions, including input power fluctuations caused by changes in sunlight intensity. The results demonstrate that the bidirectional DC-DC converter effectively operates in charging and discharging modes, maintaining a stable 24V voltage in the DC bus and providing optimal charging performance for the battery.